2021
DOI: 10.1002/anie.202105413
|View full text |Cite
|
Sign up to set email alerts
|

Phase Engineering of Cesium Manganese Bromides Nanocrystals with Color‐Tunable Emission

Abstract: For display applications, it is highly desirable to obtain tunable red/green/blue emission. However, lead‐free perovskite nanocrystals (NCs) generally exhibit broadband emission with poor color purity. Herein, we developed a unique phase transition strategy to engineer the emission color of lead‐free cesium manganese bromides NCs and we can achieve a tunable red/green/blue emission with high color purity in these NCs. Such phase transition can be triggered by isopropanol: from one dimensional (1D) CsMnBr3 NCs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
106
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(112 citation statements)
references
References 49 publications
4
106
2
Order By: Relevance
“…The elongated Mn–Mn distance can lead to a coupled vibronic state such as self-trapped excitation, which is the cause of long, microsecond-scale lifetime. 18 The TRPL decay times for both types of non-filtered and filtered Cs 3 MnBr 5 powder phosphors are 0.31 and 0.34 ms, respectively, found by fitting the decay curves using a single exponential equation, confirming the single recombination process of unique Mn 2+ ion sites in the Cs 3 MnBr 5 structure. 14 Compared to the TRPL decay time in excited states of high PLQY filtered sample, TRPL decay time in excited states of low PLQY unfiltered powders were slightly faster due to decreased radiative decay channels in lower efficiency samples.…”
Section: Resultsmentioning
confidence: 64%
See 2 more Smart Citations
“…The elongated Mn–Mn distance can lead to a coupled vibronic state such as self-trapped excitation, which is the cause of long, microsecond-scale lifetime. 18 The TRPL decay times for both types of non-filtered and filtered Cs 3 MnBr 5 powder phosphors are 0.31 and 0.34 ms, respectively, found by fitting the decay curves using a single exponential equation, confirming the single recombination process of unique Mn 2+ ion sites in the Cs 3 MnBr 5 structure. 14 Compared to the TRPL decay time in excited states of high PLQY filtered sample, TRPL decay time in excited states of low PLQY unfiltered powders were slightly faster due to decreased radiative decay channels in lower efficiency samples.…”
Section: Resultsmentioning
confidence: 64%
“…Figure 2 d shows that the PL excitation (PLE) spectra are well matched with those of previously reported Cs 3 MnBr 5 powder phosphors. 16 − 18 These PLE spectra are also monitored at emission levels of 520 nm. All PLE spectra show three similar bands at 280, 365, and 466 nm, which originate from the different levels of energy splitting of 4 T 1 excited state under the tetrahedrally coordinated environment in the Cs 3 MnBr 5 crystal structure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Solid-state luminescent switching (SSLS) is of great interest and importance for adjustable light emitting diodes (LEDs), luminescent anticounterfeiting, imaging, sensors, and so forth. The switching can be realized by stimulation such as chemical vapor, mechanical force, and heat treatment. , In particular, the solvent-responsive structural transformation can be applied to gas sensing, anticounterfeiting, and rewritable luminescent paper arising from the solvatochromic PL. ,, For instance, Yam et al recently reported the luminescence color change in a gold-sulfido cluster accompanied by single-crystal-to-single-crystal (SCSC) transition under the selective stimulation of benzene/cyclohexane vapor . The 0D OIMHs can be excellent host materials for study of SSLS upon stimulation of small molecules.…”
Section: Introductionmentioning
confidence: 99%
“…The ET efficiency from Mn 2+ to FEs is calculated to be 29.1% based on the lifetime variation of 4 T 1 -6 A 1 transition from 1.96 ms in (BTPP) 2 MnCl 4 to 1.39 ms in (BTPP) 2 MnCl 4 :2.0%Sb (Figure 2d; Figure S10a, Supporting Information). [24] Such an energy compensation thus prevents the intrinsic thermal quenching of STE emission in (BTPP) 2 MnCl 4 :2.0%Sb. [25] Considering the broadband emission with high PLQY, outstanding PL thermal stability, and chemical stability (Figure S24, Supporting Information), orange-emissive (BTPP) 2 MnCl 4 :2.0%Sb is mixed with commercial blue phosphor BaMgAl 10 O 17 : Eu 2+ (BAM: Eu 2+ ) and green silicate phosphor (Sr,Ba) 2 SiO 4 : Eu 2+ , and then the mixture is coated on a commercial 365 nm UV chip to fabricate the WLED device.…”
Section: Resultsmentioning
confidence: 99%